Crustal and Thermal Heterogeneities Across the Fram Strait and the Svalbard Margin. Issue 10 (6th October 2022) - Dumais, M.‐A.; Gernigon, L.; Olesen, O.; Lim, A.; Johansen, S. E.; Brönner, M.
Abstract: The lithospheric structure of the Fram Strait and the extent from the Knipovich Ridge to the Barents Sea shelf and Svalbard are poorly understood. Several multi‐geophysical investigations from various campaigns since the 90s along the Western Barents Sea margin and the Northeast Greenland margin resulted in insufficient and contradicting interpretations of the crustal and upper mantle settings in the oceanic and continental domains. New airborne magnetic data across the Knipovich Ridge and west of Svalbard provide new insights, reveal the complexity of the seafloor spreading history of the Arctic Atlantic Ocean, and indicate a European‐Eurasian continent‐ocean boundary located ∼150 km farther west than previously suggested. This new location of the continent‐ocean boundary prompted to revise the existing 2‐D seismic interpretations in terms of crustal domains and tectono‐stratigraphic setting. This is tested using joint 2‐D gravity and magnetic field modeling to derive an improved crust‐mantle model of the study. One recently acquired combined 2‐D controlled source electromagnetic/magneto‐telluric (CSEM/MT) profile across the Mohns Ridge was also modeled with potential field data and provided new insights into the tectonic settings of the crust and the mantle thermal anomalies. This study proposes to unify the various seismic and CSEM/MT interpretations using the new aeromagnetic compilation. Plain Language Summary: The opening of the Fram Strait between Svalbard and Greenland is still poorly understood. Studying the seafloor spreading of the Knipovich Ridge is central to understand the development history of this key area located between the Northeast Atlantic and Arctic oceans. New high‐resolution magnetic data flown above the sea reveal the complexity of the seafloor spreading history of the area. The extent of the seafloor spreading is smaller than previously suggested. The new airborne magnetic data are modeled and tested to derive an improved crust‐mantle model to better understand the development of this key area in the High Arctic. Key Points: Potential field 2‐D forward models delineate the crustal domains and revise the continent‐ocean boundary Magnetization in the oceanic domain is linked to the presence of volcanoes and bathymetric highs in the rift valley of the Knipovich Ridge A wide transition lithospheric domain without striped magnetic anomalies is delineated